Training paramedics in focussed echo in life support. (December 2015) - Booth, Katherine L.; Reed, Matthew J.; Brady, Shirin; Cranfield, Kristina R.; Kishen, Ravin; Letham, Katy; McAlpine, Graeme; Murray, Douglas B.; Wilson, Emma-Beth; Wilson, Mike; Short, Steven; Clegg, Gareth R.
Abstract : Objectives: The aim of this study was to determine whether paramedics can be trained to perform and interpret focussed Echo in Life Support (ELS) for the assessment of cardiac movement and the recognition of reversible causes of cardiac arrest. Methods: This study is a prospective observational pilot study. Data were collected during a 1-day course training 11 paramedics to perform ELS scans on healthy volunteers. The students were assessed on image acquisition skills and theoretical knowledge (including interpretation). Level 1 ultrasound-trained emergency medicine physicians undertook the training and assessment. Results: All paramedics could obtain images in the parasternal and subxiphoid views. When performing scans in the 10-s pulse check window, 88% of attempts in both views were successful (subxiphoid mean image quality 3.8 out of 5, parasternal 4.0). Theoretical knowledge improved (mean precourse score 54%, postcourse score 89%; P <0.001). There was no apparent association between theoretical and practical performances. At 10 weeks, theoretical knowledge was nonsignificantly reduced (82%; P =0.13) but less when compared with practical performance (75% subxiphoid success, mean quality 3.0; 25% parasternal success, mean quality 4.0). Conclusion: Paramedics can perform focused ELS, integrate attempts into simulated cardiac arrest scenarios and retain some of this knowledge. Further work is required to assess the feasibility of incorporating this into real-world cardiac arrest management.